2010
DOI: 10.1111/j.1559-1816.2010.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Prejudiced People Perceive More Community Support for Their Views: The Role of Own, Media, and Peer Attitudes in Perceived Consensus

Abstract: People often overestimate others' support for their views (false consensus effect). Recent research has shown that this is particularly marked in the relation between perceived consensus and prejudice. The current research asked whether this partly arises in an in‐group stereotype of the community as prejudiced. We investigated relations between different sources of normative information (self, media, peers), estimates of community attitudes, and perceived consensus in a sample of 135 community members. Media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…The public intolerance of racist behavior can have a vital contextual effect on subsequent acts of racism, but also on attitudes. Watt and Larkin (2010) found that higher levels of prejudice are associated with increased false consensus effects, such that highly prejudiced individuals overestimate support for their racist views to a greater extent than less prejudiced individuals. People who perceive themselves to be in the majority are more forthright in expressing racist opinions, less prepared to compromise, and less likely to modify their views, than those who perceive themselves to be in the minority (Watt & Larkin, 2010).…”
Section: Outcomes Of Bystander Anti‐racismmentioning
confidence: 96%
See 1 more Smart Citation
“…The public intolerance of racist behavior can have a vital contextual effect on subsequent acts of racism, but also on attitudes. Watt and Larkin (2010) found that higher levels of prejudice are associated with increased false consensus effects, such that highly prejudiced individuals overestimate support for their racist views to a greater extent than less prejudiced individuals. People who perceive themselves to be in the majority are more forthright in expressing racist opinions, less prepared to compromise, and less likely to modify their views, than those who perceive themselves to be in the minority (Watt & Larkin, 2010).…”
Section: Outcomes Of Bystander Anti‐racismmentioning
confidence: 96%
“…Watt and Larkin (2010) found that higher levels of prejudice are associated with increased false consensus effects, such that highly prejudiced individuals overestimate support for their racist views to a greater extent than less prejudiced individuals. People who perceive themselves to be in the majority are more forthright in expressing racist opinions, less prepared to compromise, and less likely to modify their views, than those who perceive themselves to be in the minority (Watt & Larkin, 2010). Public condemnation through bystander anti‐racism can potentially combat “false consensus effects” that result from individuals overestimating general community support for their racist views (Pedersen, Walker, Paradies, & Guerin, 2011).…”
Section: Outcomes Of Bystander Anti‐racismmentioning
confidence: 96%
“…These views are not accurate; research finds that non-prejudiced people are more likely to able to accurately estimate the level of support of their opinion in the community . This finding has been replicated across other cultural groups; for example, Indigenous Australians (Watt & Larkin, 2010), and with regard to asylum seeker policy (Hartley & Pedersen, 2006). Another study found a positive relationship between prejudice and perceived cultural norms to reduce the number of asylum seekers (Louis, Duck, Terry, Schuller, & Lalonde, 2007).…”
Section: Consensusmentioning
confidence: 80%
“…We believe this effort was worthwhile because, while there is considerable evidence that social norms influence the expression of prejudice (Crandall & Eshleman, 2003; Gervais, 2011; Sechrist & Stangor, 2011; Watt & Larkin, 2010), there is little empirical evidence about how stigmatized people may be affected by the social ecologies in which they live. The present study indicates that community approval for behaviors associated with members of a stigmatized group may set the stage for perceived stigmatization by people in that stigmatized group.…”
Section: Discussionmentioning
confidence: 99%